1987
DOI: 10.3109/00016488709134702
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Ossicular Vibration Ratio in Human Temporal Bones by Use of a Video Measuring System

Abstract: Vibration modes of the ossicles and the lever function were studied in human cadaver temporal bones with an intact cochlea. After placing tiny steel spheres on the ossicles, ossicular vibration to a sound stimulus was measured by observing the displacements of the spheres under a microscope with strobe illumination by means of a video measuring system. The lever ratio varied from 1.9 at 0.6 kHz (minimum) to a peak of 6 near 2 kHz. This relatively high lever ratio at higher frequencies was considered to be caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1
3

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 7 publications
9
55
1
3
Order By: Relevance
“…46,47,[71][72][73] However, significant manubrial bending was not observed in the guinea pig ear, over the measured range of up to 45 kHz. 70 Flexibility within the human middle-ear apparatus Although movement at the human malleo-incudal joint at 'physiological' sound pressure levels has long been regarded as negligible, [74][75][76][77] 80 This malleo-incudal flexibility appears to be sufficient to explain the fact that tympanic membrane (umbo) velocity changes little with stapes fixation in humans, such that stapes fixation cannot be reliably diagnosed using tympanometry. 81 Flexibility elsewhere in the human ear in response to acoustic stimulation has been less extensively examined.…”
Section: Mammalian Middle Earsmentioning
confidence: 99%
“…46,47,[71][72][73] However, significant manubrial bending was not observed in the guinea pig ear, over the measured range of up to 45 kHz. 70 Flexibility within the human middle-ear apparatus Although movement at the human malleo-incudal joint at 'physiological' sound pressure levels has long been regarded as negligible, [74][75][76][77] 80 This malleo-incudal flexibility appears to be sufficient to explain the fact that tympanic membrane (umbo) velocity changes little with stapes fixation in humans, such that stapes fixation cannot be reliably diagnosed using tympanometry. 81 Flexibility elsewhere in the human ear in response to acoustic stimulation has been less extensively examined.…”
Section: Mammalian Middle Earsmentioning
confidence: 99%
“…3) and the displacement amplitude at the center of the tympanic membrane of the artificial middle ear, which is obtained when a constant current of 10 mA is applied to the driving coil, are also shown. This artificial middle ear was made so as to have a resonance frequency of 0.8 kHz because Gyo et al (16) and Hato et al (17) reported that the resonance frequency of the middle ear of human temporal bones was between 0.7 and 1.0 kHz.…”
Section: Equivalent Sound Pressurementioning
confidence: 99%
“…Both authors used temporal bones (TBs) with drained cochleae in their studies. Therefore, their measurements did not represent physiologic motions, since it has been shown in more recent experiments that movement patterns of the stapes footplate change when the cochlea is drained (Gyo et al 1987;Hato et al 2003). Gundersen (1971) showed that a piston-like motion pattern was preserved up to 2 kHz, but movements of the stapes in an "uneven manner" appeared at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in measurement techniques and methods have shown complex modes of the stapes motions more clearly. Using a video measuring system, Gyo et al (1987) observed predominant piston-like movements only at low frequencies and complex movements at higher frequencies. Other studies in human and animals are in accordance with these findings (Asai et al 1999;Decraemer & Khanna 1999;Voss et al 2000;Hato et al 2003;Stenfelt and Goode 2005;Decraemer et al 2007;Ravicz et al 2008;Sim et al 2010a).…”
Section: Introductionmentioning
confidence: 99%